Assessing the risk of carbon dioxide emissions from blue carbon ecosystems. Issue 5 (15th May 2017) - Lovelock, Catherine E; Atwood, Trisha; Baldock, Jeff; Duarte, Carlos M; Hickey, Sharyn; Lavery, Paul S; Masque, Pere; Macreadie, Peter I; Ricart, Aurora M; Serrano, Oscar; Steven, Andy
Abstract : "Blue carbon" ecosystems, which include tidal marshes, mangrove forests, and seagrass meadows, have large stocks of organic carbon (Corg ) in their soils. These carbon stocks are vulnerable to decomposition and – if degraded – can be released to the atmosphere in the form of CO2 . We present a framework to help assess the relative risk of CO2 emissions from degraded soils, thereby supporting inclusion of soil Corg into blue carbon projects and establishing a means to prioritize management for their carbon values. Assessing the risk of CO2 emissions after various kinds of disturbances can be accomplished through knowledge of both the size of the soil Corg stock at a site and the likelihood that the soil Corg will decompose to CO2 .